Structural, elastic and optical properties of zinc-alumino-borosilicate doped gadolinium oxide glass-ceramics - Ismail, Nur Atikah Nazihah (2022)
In recent years, researchers are developing a great interest towards the fabrication and synthesizing willemite (Zn2SiO4) glass-ceramics. However, intensity luminescence of willemite based glass ceramic doped with gadolinium oxide (Gd2O3) is less reported. Hence, this study is focusing on fabricate and synthesized willemite based glass-ceramics using Gd2O3 as dopant. The Gd2O3 doped zinc-alumino-borosilicate (ZnO-Al2O3-B2O3-SiO2) glass system were synthesized via the melt-quenching approach using composition (60–x)ZnO– 5Al2O3–15B2O3–20SiO2:x(Gd2O3)(x = 0, 0.5, 1.0, 2.0 and 3.0 mol%) and willemite-based glass-ceramics were obtained from these precursor glasses through a controlled crystallization process. According to all analysis, the best willemite based glass-ceramic has been selected from the glass system when doped with 3 mol% of Gd2O3 and temperature at 800 °C. XRD and FESEM methods were also used to analyze the structural properties of precursor glass, the formation of willemite crystal phase, shape, and size as crystallization temperatures increased. The average approximated crystallite size determined by XRD is in the 50-70 nm range. The structural properties of glass and glass-ceramics were assessed using FTIR spectroscopy. The infrared spectra studies reveal the existence of SiO2 and ZnO4 vibrational groups indicating the establishment of the willemite crystal phase. As for elastic analysis, the values for experimental elastic moduli were obtained from ultrasonic velocities measurement by using the non-destructive ultrasonic technique. The longitudinal and shear velocities vary from 4798 to 6976 m/s and 2991 to 3082 m/s, respectively. The experimental elastic moduli (longitudinal modulus (L), shear modulus (G), bulk modulus (K) and Young’s modulus (E)) increases from 94.60 to 202.98 GPa, 36.77 to 39.61 GPa, 45.56 to 150.17 GPa and 86.94 to 109.22 GPa, respectively. In addition, the optical band willemite based glass-ceramics doped with Gd2O3 fluctuate from 3.64 to 3.38 eV due to structural rearrangement of network. The emission spectra of gadolinium ions show the strong emission peak at wavelengths of 425, 447, 462, 485, and 530 nm. The willemite phase shows prominent green emission spectra located at 530 nm. These emission spectra produce when the dopant content and heat treatment temperatures increase, the luminescence performance of the glassceramics also improves. The incorporation of gadolinium ions into the willemite crystals as heat treatment temperatures increase affect the intensity of the emission. The structural, elastic and optical properties of willemite glassceramics enhanced with the addition of Gd2O3 as dopant.